PERKEMBANGAN SASTRA DI ERA BANI UMAYYAH (ANALISA KRITIS STRUKTURALISME-GENETIK) - Muzakki, Akhmad (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2006)
Sociologically, literature is a reflection of culture environment and as a dialectical text between the author and his social condition. Due to this fact, to understand and interpret literary works, we not only need to know the literary theory but also the external problems, such as, those of religion, society, and politics. In other words, it can be said that a literary work is a very complicated work because basically it is the reflection of human life with various dimensions that influence it.